2020
DOI: 10.1590/2237-6089-2019-0098
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction in students from an educational institution in Southern Brazil: prevalence and associated factors

Abstract: Objective To evaluate the prevalence of Internet addiction (IA) and its associated factors among students at an Educational Institution in Southern Brazil. Method This is a cross-sectional study, targeting a sample of students aged from 14 to 20 years. They were selected by random sampling to be representative of the 4038 students enrolled at the institute at the time. IA was assessed using the Internet Addiction Test (IAT). Screening for anxiety and/or depressive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(110 reference statements)
0
8
0
2
Order By: Relevance
“…Based on all the above-mentioned findings, it was possible to agree that the co-existence of internet addiction and depressive symptoms, anxiety symptoms, and stress in college students indicates that internet addiction is associated with other psychological problems ( 38 ). From the opposite point of view, students who were psychologically well were less likely to be addicted ( 35 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on all the above-mentioned findings, it was possible to agree that the co-existence of internet addiction and depressive symptoms, anxiety symptoms, and stress in college students indicates that internet addiction is associated with other psychological problems ( 38 ). From the opposite point of view, students who were psychologically well were less likely to be addicted ( 35 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, respondents could select one of the following answers for each of the 10 items: never-−0, almost never-−1, sometimes-−2, fairly often-−3, very often-−4. The ranges of the total PSS-10 score indicated: low stress (0-13), moderate stress (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Accordingly, the higher the total score, the more severe the psychological distress.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to highlight the high SPA prevalence before and during lockdown for the sample evaluated. Other Brazilian studies have also shown high SPA and internet addiction prevalence [33][34][35] . Although there are comparison limitations regarding inclusion and exclusion criteria and differences on SPA assessment scales, this finding reinforces the importance of preventive and harm reduction health policies.…”
Section: Discussionmentioning
confidence: 99%